Study protocol for a randomised controlled trial to investigate the effectiveness of thoracic epidural and paravertebral blockade in reducing chronic post-thoracotomy pain: 2 (TOPIC 2) - Ben Shelley; Andreas Goebel; Stephen Grant; Louise Jackson; Hugh Jarrett; Marcus Jepson; Amy Kerr; Nandor Marczin; Rajnikant Mehta; Teresa Melody; Lee Middleton; Babu Naidu; et al. (Trials, 2023)
Abstract Background Thoracotomy is considered one of the most painful surgical procedures and can cause debilitating chronic post-surgical pain lasting months or years postoperatively. Aggressive management of acute pain resulting from thoracotomy may reduce the likelihood of developing chronic pain. This trial compares the two most commonly used modes of acute analgesia provision at the time of thoracotomy (thoracic epidural blockade (TEB) and paravertebral blockade (PVB)) in terms of their clinical and cost-effectiveness in preventing chronic post-thoracotomy pain. Methods TOPIC 2 is a multi-centre, open-label, parallel group, superiority, randomised controlled trial, with an internal pilot investigating the use of TEB and PVB in 1026 adult (≥ 18 years old) patients undergoing thoracotomy in up to 20 thoracic centres throughout the UK. Patients (N = 1026) will be randomised in a 1:1 ratio to receive either TEB or PVB. During the first year, the trial will include an integrated QuinteT (Qualitative Research Integrated into Trials) Recruitment Intervention (QRI) with the aim of optimising recruitment and informed consent. The primary outcome is the incidence of chronic post-surgical pain at 6 months post-randomisation defined as ‘worst chest pain over the last week’ equating to a visual analogue score greater than or equal to 40 mm indicating at least a moderate level of pain. Secondary outcomes include acute pain, complications of regional analgesia and surgery, health-related quality of life, mortality and a health economic analysis. Discussion Both TEB and PVB have been demonstrated to be effective in the prevention of acute pain following thoracotomy and nationally practice is divided. Identification of which mode of analgesia is both clinically and cost-effective in preventing chronic post-thoracotomy pain could ameliorate the debilitating effects of chronic pain, improving health-related quality of life, facilitating return to work and caring responsibilities and resulting in a cost saving to the NHS. Trial registration NCT03677856 [ClinicalTrials.gov] registered September 19, 2018. https://clinicaltrials.gov/ct2/show/NCT03677856 . First patient recruited 8 January 2019.